ANÁLISE DO ÍNDICE DE REDUÇÃO SONORA PONDERADO E DO ESPAÇAMENTO IDEAIS PARA UM SISTEMA DE PAREDE CONSTITUÍDO POR UM PAINEL DUPLO DE OSB E FIBRA DE COCO - Ribeiro, Paulo; Niemeyer, Maria; Silvoso, Marcos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This research has been carried out in order to identify some sound reduction indexes ( ) and ideal spacings (d) for wall systems made out of double OSB panel filled with coir. The method consisted of calculating this ideal spacing (d) between panels for a wide range of possible variables configuration related to such number and gathering the souces that make up the current State-of-the-Art regarding the subject at hands. The variables used in this study in order to perform the aforementioned calculations and outlined by this information gathering were the followinf ones: partition's hard component thickness, partition's hard comonet density, partition's hard component resonance frequency (f°) and partition's hard component surface mass(Ms¹ e Ms²) . It was concluded through this study that the sound reduction index ( ) value varies according to each one of the used references without having reached any sort of compromise. When it came to the ideal spacing (d) between panels (d), it was concluded that for each variables configuration, a distinct ideal spacing (d) can be found. T frequency ( ) leads to a more efficient sound reduction index ( ) in any of the cases mentioned in this paper.